Interaction of metal nanoparticles with recombinant arginine kinase from Trypanosoma brucei: Thermodynamic and spectrofluorimetric evaluation - Adeyemi, O.S.; Whiteley, C.G. (Biochimica et biophysica acta, 2014)
Trypanosoma brucei, responsible for African sleeping sickness, is a lethal parasite against which there is need for new drug protocols. It is therefore relevant to attack possible biomedical targets with specific preparations and since arginine kinase does not occur in humans but is present in the parasite it becomes a suitable target. Fluorescence quenching, thermodynamic analysis and FRET have shown that arginine kinase from T. brucei interacted with silver or gold nanoparticles. The enzyme only had one binding site. At 25°C the dissociation (Kd) and Stern–Volmer constants (KSV) were 15.2nM, 0.058nM−1 [Ag]; and 43.5nM, 0.052nM−1 [Au] and these decreased to 11.2nM, 0.041nM−1 [Ag]; and 24.2nM, 0.039nM−1 [Au] at 30°C illustrating static quenching and the formation of a non-fluorescent fluorophore–nanoparticle complex. Silver nanoparticles bound to arginine kinase with greater affinity, enhanced fluorescence quenching and easier access to tryptophan molecules than gold. Negative ΔH and ΔG values implied that the interaction of both Ag and Au nanoparticles with arginine kinase was spontaneous with electrostatic forces. FRET confirmed that the nanoparticles were bound 2.11nm [Ag] and 2.26nm [Au] from a single surface tryptophan residue. The nanoparticles bind close to the arginine substrate through a cysteine residue that controls the electrophilic and nucleophilic characters of the substrate arginine–guanidinium group crucial for enzymatic phosphoryl transfer between ADP and ATP. The nanoparticles of silver and gold interact with arginine kinase from T. brucei and may prove to have far reaching consequences in clinical trials. Proposed structure of the binding sites for TbAK showing the interaction of silver/gold nanoparticles through Cys271, interfering with N1 of the arginine substrate. The interatomic distance between the thiolate atom of Cys271 and N1 of the arginine substrate is 3.3Å. The interatomic distance between Trp104 and N1 is 22.2Å while that distance between Trp104 and bound Ag/Au nanoparticles is 21.1Å and 22.6Å respectively. Nitrate not shown. [Display omitted] •Interaction of silver and gold nanoparticles with arginine kinase from Trypanosoma brucei by fluorescence quenching•FRET showed that the nanoparticles were bound 2.11nm [Ag] and 2.26nm [Au] from a single surface tryptophan.•The nanoparticles bind close to the arginine substrate through a cysteine residue crucial for the enzymes reaction mechanism.•These nanoparticles could have implications against trypanosomiasis in clinical trials.